Spatial Analysis of Agricultural Landscape and Hymenoptera Biodiversity at Cianjur Watershed - YAHER WANDI; SYAFRIDA MANUWOTO; DAMAYANTI BUCHORI; PURNAMA HIDAYAT; LILIK BUDIPRASETYO (Bogor Agricultural University, Indonesia, 2006)
Hymenoptera is one of the four largest insect order (the other three are Coleoptera, Diptera, and Lepidoptera). There are curerently over 115 000 described Hymenoptera species. It is clear that Hymenoptera is one of the major components of insect biodiversity. However, Hymenoptera biodiversity is affected by ecology, environment, and ecosystem management. In an agricultural areas, the spatial structure, habitat diversity, and habitat composition may vary from cleared landscapes to structurally rich landscape. Thus, it is very likely that such large-scale spatial patterns (landscape effects) may influence local biodiversity and ecological functions. Therefore, the objective of this research were to study diversity and configuration elements of agricultural landscapes at Cianjur Watershed with geographical information sytems (GIS) and its influence on Hymenoptera biodiversity. The structural differences between agricultural landscapes of Nyalindung, Gasol, and Selajambe were characterized by patch analyst with ArcView 3.2 of digital land use data. Results indicated that class of land uses of Cianjur Watershed landscape were housing, mixed gardens, talun and rice, vegetable, and corn fields. Landscape structure influenced the biodiversity of Hymenoptera. Species richness and the species diversity were higher in Nyalindung landscape compare to Gasol and Selajambe landscape. Key words: diversity, Hymenoptera, landscape, watershed, GIS